To evaluate the diagnostic value of protein: creatinine ratio in a single voided urine sample for quantitation of proteinuria compared to those of a 24-hour urine sample in patients with preeclampsia - Hossain, S; Ghosh, A; Chatterjee, A; Sarkar, G; Mondal, SS (Journal of College of Medical Sciences-Nepal, 2014)
Objective: This study was done to evaluate the diagnostic value of protein: creatinine ratio in a single voided urine sample for quantitation of proteinuria compared to those of a 24 hour urine sample in patients with preeclampsia. Methods: A prospective simple random sample study was done on the hypertensive pregnant women attending the antenatal clinic or admitted in Department of Obstetrics and Gynaecology. It included all women being evaluated for preeclampsia, regardless of the alerting sign or symptom, suspected severity or co-morbid conditions. The main measures were the urinary protein to urinary creatinine ratio by random (spot) direct measurement and the 24-h urinary protein excretion by a 24-h urine collection. The data obtained was statistically analyzed. Results: Out of the 78 patients with gestational hypertension included in our study 48 patients had significant proteinuria (e”300mg/day). Only 2 patients had proteinuria of the range of greater than 3500mg. Among the patients, 50 had a positive protein: creatinine ratio (e”0.3) while 28 patients had a negative protein: creatinine ratio (<0.3). The P: C ratio was able to correctly identify 44 out of 48 patients with significant proteinuria (when the comparison is made with the gold-standard test; i.e., 24-hour urine protein). It could also identify 24 out of 30 patients without significant proteinuria as compared to the gold-standard test. In this study, the Protein: Creatinine ratio with a sensitivity of 91.67%, a specificity of 80%, positive predictive values 88% and the negative predictive values 85.71%. Conclusions: Our data suggests that the protein: creatinine ratio in single voided urine is a highly accurate test (p value < 0.0000001) for discriminating between insignificant and significant proteinuria. Based on the above findings we conclude that a random urine protein excretion predicts the amount of 24- hour urine protein excretion with high accuracy. This could be a reasonable alternative to the 24-hour urine collection for detection of significant proteinuria in hospitalised pregnant women with suspected preeclampsia. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 45-53 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9687